HUBUNGAN PERILAKU DENGAN INFEKSI SOIL TRANSMITTED HELMINTHS PADA ANAK SEKOLAH DASAR MI ASAS ISLAM KALIBENING, SALATIGA - Liena, Sofiana (Universitas Ahmad Dahlan, 2010)
Background : Occurence of Soil Transmitted Helminths infection in Indonesia still very high. That wormy number at elementary school student are 60-80%. Soil Transmitted Helminths infection is a health problem in tropical and subtropical regions. The number of patients infected with more than one species of intestinal worms such as Ascaris, Trichuris and hookworm. In the tropics, the soil moist and protected from sunlight is a good condition to continue the transmission of Ascaris continuously. Clay is a good place for development and remain infective Ascaris eggs around the puddle of water because of drought escape. When exposed to rain, water mixed with soil to spread to vegetables or fruits are eaten or later come flying through the air and will contaminate the environment. In areas with poor sanitation conditions and dense population prevalence will increase. Her case is more frequent in children mainly aged 5-9 years compared with adults. Another contributing factor is the knowledge, attitudes, and behavior of healthy people against infections Soil Transmitted Helminths. This study to investigate the correltion between the behavior with the Soil Transmitted Helminths infection in children of primary school. Method : It is an analytic and observational study with cross sectional design. The data is collected using faecal survey is using Kato Katz method and interview is using questionnaire the 33 respondents. Result : The result of the study showed that there is not any significant correlation between behavior and the Soil Transmitted Helminths infection (p=0,616) of the elemntary school children in MI Asas Islam Kalibening, Tingkir Of Salatiga District. Conclusion : There is statistically not any significant correlation between behavior and the soil transmitted Helminths infection. Keywords : Soil Transmitted Helminths, behavior.